Ambonese Arrack (Sopi): Processing and It’s Functions in Moluccan Culture - Mahulette, Ferymon (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
Sopi is a beverage used in various traditional and religious ceremonies in Moluccas. The raw materials and processing techniques of this fermented product are very diverse. The processing of sopi has been done by the ancestors of Moluccan for a long time, but information about processing this product is very limited. This research aimed to describe the techniques of sopi processing and itâ€™s functions in Moluccan culture. This study was descriptive qualitative research design. Data was collected from direct observations in five villages in differences islands, i.e. Mahia (Ambon island), Ouw (Saparua island), Sifluru (Ceram island), Wangel (Aru islands), and Yawuru (Kisar island). The processing of sopi were diverse in Moluccas. The raw materials used in the processing of sopi were saps from coconut, palm sugar, and coli trees, while the equipment of distillation were made of bamboo, plastic and pipe. Sopi was used in various traditional and religious ceremonies such as cuci negeri, panas pela, sumpah sopi and siram sopi. In general this traditional beverage is a symbol of solidarity in the Moluccans tradition. This research was expected to conserve of sopi processing culture to support the tourism in Moluccas.Â